Model Peningkatan Pendapatan Rumah Tangga Berbasis Faktor-Faktor Produksi Di Kota Medan - Rini Astuti; Isna Ardila; Linzzy Pratami Putri (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2022)
Currently, home industry business actors must be able to prepare themselves and have a good strategy in producing quality products and have an extensive marketing network, so that the products produced can be accepted by the market or consumers, so that small industrial businesses can increase family income. This study aims to determine how the model of increasing household income based on factors of production in the city of Medan. The specific objectives of this study are 1) to design a model of increasing household income based on factors of production in the city of Medan. 2) determine the production factors that support the increase in household income in producing products. This research is a basic research because in this research a modeling process is carried out to obtain the most appropriate model in increasing household income based on production factors in home industries in Medan City. The research population is the target population, namely the home industry business in the city of Medan, which is a manufacturing business with a capital scale of Rp. 2000.000.000,- This research is quantitative descriptive, using Structural Equation Modeling (SEM) research method to analyze home industry business based on production factors and causality test to determine income increase model based on production factors. Data analysis techniques will be assisted with AMOS and SPSS tools. The results of the structural model research show that the dominant factors affecting family income are capital, human resources, technology and marketing.